1996
DOI: 10.1002/ana.410390317
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial defect in Huntington's disease caudate nucleus

Abstract: References 1. Courchesne E, Yeung-Courchesne R, Press GA, et al. Hypoplasia of cerebellar vermal lobules VI md VII in autism. N Engl J Med 1988;318:1349-1354 2. Mirakanii JW, Courchesne E, Press GA. et al. Keduced cerehellar hemisphere size and its relationship to neural hypoplasia in autism. Arch Neurol 1989;46:689-694 3 . Courchesne E. Neuroanatomic imaging in autism. Pediatrics 1991;87:781-790 4. Courchesne E, Saitoh 0. Yeung-Courchesne R, et al. Abnormality of crrebellar vernii;in lobules V1 and VII in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

29
396
2
6

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 676 publications
(433 citation statements)
references
References 17 publications
29
396
2
6
Order By: Relevance
“…We suggested that the genetic defect may lead to impaired oxidative phosphorylation, which may play a critical role in pathogenesis. We and others found a decrease in mitochondrial complex 11-111 activity in HD basal ganglia (Gu et al, 1996;Browne et al, 1997). Furthermore, using MRI spectroscopy, we found increased lactate levels within the HD cerebral cortex and in basal ganglia, as well as an increase in phosphocreatine to inorganic phosphate ratio in HD resting muscle (Koroshetz et al, 1997;Jenkins et al, 1998).…”
supporting
confidence: 67%
“…We suggested that the genetic defect may lead to impaired oxidative phosphorylation, which may play a critical role in pathogenesis. We and others found a decrease in mitochondrial complex 11-111 activity in HD basal ganglia (Gu et al, 1996;Browne et al, 1997). Furthermore, using MRI spectroscopy, we found increased lactate levels within the HD cerebral cortex and in basal ganglia, as well as an increase in phosphocreatine to inorganic phosphate ratio in HD resting muscle (Koroshetz et al, 1997;Jenkins et al, 1998).…”
supporting
confidence: 67%
“…Accordingly, the expression of two subunits of the complex II is decreased in the striatum of HD patients, affecting the dehydrogenase activity of the complex (Benchoua et al, 2006). A small decrease in complex IV in brain samples was also reported (Browne et al, 1997;Gu et al, 1996;Schapira, 1998;Tabrizi et al, 1999).…”
Section: Introductionmentioning
confidence: 82%
“…In platelets from HD patients, some authors found a decrease in complex I activity (Parker et al, 1990), whereas others reported no changes in the activity of mitochondrial complexes (Gu et al, 1996;Powers et al, 2007a). Moreover, the phosphocreatine/ inorganic phosphate ratio was significantly decreased in resting muscle (Koroshetz et al, 1997) of HD patients, evidencing bioenergetic changes in HD peripheral tissues.…”
Section: Introductionmentioning
confidence: 97%
“…*Po0.05, **Po0.01 versus control myoblasts changes reported by morphological analyses of human HD skeletal muscle. 8 Previous reports have described altered mitochondrial oxidative metabolism in brain and peripheral tissues of HD subjects [6][7][8][9]19 and increased mitochondrial depolarization after stress conditions in both fibroblasts and lymphoblasts from HD subjects. 20,21 In our cell model, we observed mitochondrial DC m dissipation and cytochrome c release even under normal growth conditions.…”
Section: Discussionmentioning
confidence: 99%